Predictive indicators of overuse injuries in adolescent endurance athletes - Martinez-Silvan, D.; Diaz-Ocejo, J.; Murray, A. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To analyze the influence of training exposure and the utility of self-report questionnaires on predicting overuse injuries in adolescent endurance athletes. Methods: Five adolescent male endurance athletes (15.7 ± 1.4 y) from a full-time sports academy answered 2 questionnaires (Recovery Cue; RC-q and Oslo Sports Trauma Research questionnaire; OSTRC-q) on a weekly basis for 1 season (37 wk) to detect signs of overtraining and underrecovery (RC-q) and early symptoms of lower-limb injuries (OSTRC-q). All overuse injuries were retrospectively analyzed to detect which variations in the questionnaires in the weeks preceding injury were best associated. Overuse incidence rates were calculated based on training exposure. Results: Lower-limb overuse injuries accounted for 73% of total injuries. The incidence rate for overuse training-related injuries was 10 injuries/1000 h. Strong correlations were observed between individual running exposure and overuse injury incidence (r2 = .66), number of overuse injuries (r2 = .69), and days lost (r2 = .66). A change of 20% or more in the RC-q score in the preceding week was associated with 67% of the lower-limb overuse injuries. Musculoskeletal symptoms were only detected in advance by the OSTRC-q in 27% of the episodes. Conclusion: Training exposure (especially running exposure) was shown to be related to overuse injuries, suggesting that monitoring training load is a key factor for injury prevention. Worsening scores in the RC-q (but not the OSTRC) may be an indicator of overuse injury in adolescent endurance runners when used longitudinally.